LEANING OUT;A FAIRER FUTURE FOR WOMEN AT WORK IN AUSTRALIA. - KRISTINE ZIWICA ([S.l.] : HARDIE GRANT BOOKS, 2022)
From Lean In-style feminism to the Great Resignation, this book deconstructs the recent history of Australian women at work and plots a collective path forward.
Intro -- Title Page -- Contents -- Author's Note -- Introduction -- 1. When Girl Power grows up -- 2. Who cares? From career feminism to care feminism -- 3. Burnout, pandemic style -- 4. 'Know your worth': The gender pay gap's big lie -- 5. The home front -- 6. Throwing babies out with the COVID bathwater -- 7. Fair game: Safety at work -- Conclusion: A new deal for women at work -- Acknowledgements -- Notes -- Copyright Page
eBooks on EBSCOhost
Keywords: Women -- Employment -- Australia; Sex discrimination against women -- Australia; Sex discrimination in employment -- Australia; Discrimination à l'égard des femmes -- Australie; Discrimination sexuelle dans l'emploi -- Australie; Labor; BUSINESS & ECONOMICS; Workplace Culture; Feminism & Feminist Theory; SOCIAL SCIENCE; Sex discrimination against women; Sex discrimination in employment; Women -- Employment; Australia